PENGARUH MEDIA POSTER TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI DI KELAS IV MI MIFTAH ASSA’ADAH KOTA TANGERANG SELATAN - Hendrawan, Belinda Bilqiis; Fatonah, Khusnul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem in this study is relates to the suboptimal writing skills of students in composing descriptive essays. This study aims to determine the impact of using poster media on the skill of writing descriptive essays in the IV MI Miftah Assa’adah in South Tangerang City. This research uses a quantitative approach with an experimental method of the one group pretest-posttest design. The population in this study consists of 38 students from class IV A. Data were collected using questionnaires and pretest-posttest. The results of the study show that the average pretest score before using the poster media was 60.92, and after using the poster media, it increased to 71.84. Furthermore, the researcher conducted a hypothesis test to determine whether poster media has an effect on students' ability to write descriptive essays. Based on the paired sample t-test, the t-value obtained was 14.106, which is greater than the t-table value of 2.026, and the significance value was 0.000, which is less than 0.05. These results indicate that H0 is rejected and H1 is accepted, meaning that poster media has an effect on students' ability to write descriptive essays in class IV at MI Miftah Assa’adah in South Tangerang City.